Machiavellianism, love of money, religiosity, and tax evasion perception relationship model: a multi-group analysis based on gender - Uun Sunarsih; Lila Nurdiana (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2024)
This study explores the relationship between Machiavellianism, love of money, religiosity, and perceptions of tax evasion, specifically focusing on gender differences. Using a convenience sampling method, the study gathered responses from 372 participants in Indonesia. The analysis revealed a significant positive relationship between Machiavellianism and the perception of tax evasion and a notable negative relationship between religiosity and the perception of tax evasion, particularly among men. In contrast, love of money was found to have no significant relationship with perceptions of tax evasion. These findings suggest that individuals with high levels of Machiavellianism tend to have a more favorable view of tax evasion. In contrast, higher levels of religiosity deter such behavior. This study contributes to understanding ethical behavior in the context of taxation. It emphasizes the need for gender-specific educational approaches and interventions to reduce tax evasion. Public interest statements This research examines the factors influencing perceptions of tax evasion, specifically focusing on Machiavellianism, love of money, and religiosity while highlighting gender differences. The findings are intended to inform policymakers and educators, helping to develop targeted interventions and educational programs that promote ethical behavior and tax compliance.